Criticism Of Epistemologyuniversal Declaration Of Human Rights :Islamic Perspective - Afdal, Afdal (2016)
HAM becomes a major trend that is very central and predicted as a form of human civilization civilized at twentieth century. The values of human rights are contained of the Universal Declaration of Human Rights ( UDHR ) upheld as a global value that must be enforced by all of the countries in the world. UDHR through UN becomes a common standard reference for measuring successful level of a country in upholding human rights. This study will answer; Howdoes it implicate the secular epistemology against the substance of the Universal Declaration of Human Rights? Besides that, How does Islam look the epistemology of Universal Declaration of Human Rights? To answer these questions, they use the library' datas by using a philosophical approach as a method oftheresearch.The model used a induction and deduction. The result of this study indicates that the secular epistemology as an foundation of UDHR's epistemology implicates for a cargo. The substance of the UDHR can be translated very freely and without limited even ignores the values of religiosity. Humans being are considered as central, source, destination and as the orientation of each human's behavior. Religion and God are not regarded as something sacred, but only considered as a complement of human life. It's free adapted by realm of privatization but not to each individual. Such a view is contrary to Islam. Islam holds that religion and God is sacred andcan not be separated from the facet of human life. God is a central, source, destination end theorientation of human behavior . Keywords: epistemology, human rights, the Islamic Human Rights,UDHR.